Determination of Salmonella enterica in biologically appropriate raw food for dogs (BARF) in Lima, Perú - Espinoza-Garate, Kely (2022)
The study aimed to determine the frequency and antibiotic resistance of Salmonella enterica isolated from biologically appropriate raw food (BARF) for dogs in Lima, Peru. In total, 124 samples belonging to 13 brands and batches of BARF-type food available in the local market were collected. The samples were transported in a cooler at 4 °C and kept frozen -18 °C until processing. Bacterial isolation and identification were carried out through biochemical tests, to finally determine antimicrobial resistance against 16 antibiotics. The frequency of S. enterica was 55.6 + 8.7% (69/124), with a statistical association (p<0.05) between the presence of Salmonella and the BARF-type food brand. No significant association (p>0.05) was found between the type of meat in the food and the diagnosis of S. enterica. The results showed 81.5% of S. enterica strains were resistant, 11.6% showed intermediate resistance, and 7.4% were sensitive to antibiotics. S. entérica has a high frequency in BARF food for dogs marketed in Lima.